Minimal sufficient balance randomization for sequential randomized controlled trial designs: results from the ESCAPE trial - Tolulope T. Sajobi; Gurbakhshash Singh; Mark W. Lowerison; Jordan Engbers; Bijoy K. Menon; Andrew M. Demchuk; Mayank Goyal; Michael D. Hill (Trials, 2017)
Abstract Background We describe the implementation of minimal sufficient balance randomization, a covariate-adaptive randomization technique, used for the “Endovascular treatment for Small Core and Anterior circulation Proximal occlusion with Emphasis on minimizing CT to recanalization times” (ESCAPE) trial. Methods The ESCAPE trial is a prospective, multicenter, randomized clinical trial that enrolled subjects with the following main inclusion criteria: less than 12 h from symptom onset, age 18 years or older, baseline NIHSS score > 5, ASPECTS score > 5 and computed tomography angiography (CTA) evidence of carotid T/L or M1-segment middle cerebral artery (MCA) occlusion, and at least moderate collaterals by CTA. Patients were randomized using a real-time, dynamic, Internet-based, minimal sufficient balance randomization method that balanced the study arms with respect to baseline covariates including age, sex, baseline NIHSS score, site of arterial occlusion, baseline ASPECTS score and treatment with intravenously administered alteplase. Results Permutation-based tests of group differences confirmed group balance across several baseline covariates including sex (p = 1.00), baseline NIHSS score (p = 0.95), site of arterial occlusion (p = 1.00), baseline ASPECTS score (p = 0.28), treatment with intravenously administered alteplase (p = 0.31), and age (p = 0.67). Conclusion Results from the ESCAPE trial demonstrate the feasibility and the benefit of this covariate adaptive randomization scheme in small-sample trials and for data monitoring endeavors. Trial registration ESCAPE trial – NCT01778335 – at www.clinicaltrials.gov . Registered on 29 January 2013.